Databases Theory and Applications: 26th Australasian Database Conference, ADC 2015, Melbourne, VIC, Australia, June 4-7, 2015. Proceedings - Sharaf, Mohamed A (Springer, 2015)
This book constitutes the refereed proceedings of the 26th Australasian Database Conference, ADC 2015, held in Melbourne, VIC, Australia, in June 2015. The 24 full papers presented together with 5 demo papers were carefully reviewed and selected from 43 submissions. The Australasian Database Conference is an annual international forum for sharing the latest research advancements and novel applications of database systems, data driven applications and data analytics between researchers and practitioners from around the globe, particularly Australia and New Zealand. The mission of ADC is to share novel research solutions to problems of today’s information society that fulfill the needs of heterogeneous applications and environments and to identify new issues and directions for future research. ADC seeks papers from academia and industry presenting research on all practical and theoretical aspects of advanced database theory and applications, as well as case studies and implementation experiences.